<meta http-equiv="refresh" content="1; url=/nojavascript/"> Rectangular to Polar Form for Equations | CK-12 Foundation
Dismiss
Skip Navigation
You are reading an older version of this FlexBook® textbook: CK-12 Trigonometry Concepts Go to the latest version.

6.6: Rectangular to Polar Form for Equations

Created by: CK-12
%
Progress
Practice Rectangular to Polar Form for Equations
Practice
Progress
%
Practice Now

You are working diligently in your math class when your teacher gives you an equation to graph:

(x + 1)^2 - (y + 2)^2 = 7

As you start to consider how to rearrange this equation, you are told that the goal of the class is to convert the equation to polar form instead of rectangular form.

Can you find a way to do this?

By the end of this Concept, you'll be able to convert this equation to polar form.

Watch This

James Sousa Example: Find the Polar Equation for a Line

Guidance

Interestingly, a rectangular coordinate system isn't the only way to plot values. A polar system can be useful. However, it will often be the case that there are one or more equations that need to be converted from rectangular to polar form. To write a rectangular equation in polar form, the conversion equations of x = r \cos \theta and y = r \sin \theta are used.

If the graph of the polar equation is the same as the graph of the rectangular equation, then the conversion has been determined correctly.

(x-2)^2+y^2=4

The rectangular equation (x - 2)^2 + y^2 = 4 represents a circle with center (2, 0) and a radius of 2 units. The polar equation r = 4 \cos \theta is a circle with center (2, 0) and a radius of 2 units.

Example A

Write the rectangular equation x^2 + y^2 = 2x in polar form.

Solution: Remember r = \sqrt{x^2 + y^2}, r^2 = x^2 + y^2 and x = r \cos \theta .

x^2 + y^2 &= 2x\\ 	r^2 &= 2(r \cos \theta) && Pythagorean \ Theorem \ and \ x = r \cos \theta\\ r^2 &= 2r \cos \theta\\ 	r &= 2 \cos \theta && Divide \ each \ side \ by \ r

Example B

Write (x - 2)^2 + y^2 = 4 in polar form.

Remember x = r \cos \theta and y = r \sin \theta .

&(x - 2)^2 + y^2 = 4\\&(r \cos \theta - 2)^2 + (r \sin \theta)^2 = 4 && x = r \cos \theta \ and \ y = r \sin \theta\\ &r^2 \cos^2 \theta - 4r \cos \theta + 4 + r^2 \sin^2 \theta = 4 && expand \ the \ terms\\&r^2 \cos^2 \theta - 4r \cos \theta + r^2 \sin^2 \theta = 0 && subtract \ 4 \ from \ each \ side\\ &r^2 \cos^2 \theta + r^2 \sin^2 \theta = 4r \cos \theta && isolate \ the \ squared \ terms\\ &r^2 (\cos^2 \theta + \sin^2 \theta) = 4r \cos \theta && factor \ r^2 -  a \ common \ factor\\ &r^2 = 4r \cos \theta && Pythagorean \ Identity\\ &r = 4 \cos \theta && Divide \ each \ side \ by \ r

Example C

Write the rectangular equation (x+4)^2 + (y-1)^2 = 17 in polar form.

&(x+4)^2 + (y-1)^2 = 17\\&(r \cos \theta + 4)^2 + (r \sin \theta - 1)^2 = 17 && x = r \cos \theta \ and \ y = r \sin \theta\\ &r^2 \cos^2 \theta + 8r \cos \theta + 16 + r^2 \sin^2 \theta - 2r \sin \theta + 1 = 17 && expand \ the \ terms\\&r^2 \cos^2 \theta + 8r \cos \theta - 2r \sin \theta + r^2 \sin^2 \theta = 0 && subtract \ 17 \ from \ each \ side\\ &r^2 \cos^2 \theta + r^2 \sin^2 \theta = -8r \cos \theta + 2r \sin \theta && isolate \ the \ squared \ terms\\ &r^2 (\cos^2 \theta + \sin^2 \theta) = -2r (4\cos \theta - \sin \theta) && factor \ r^2 -  a \ common \ factor\\ &r^2 = -2r (4\cos \theta - \sin \theta) && Pythagorean \ Identity\\ &r = -2(4\cos \theta - \sin \theta) && Divide \ each \ side \ by \ r

Vocabulary

Polar Coordinates: A set of polar coordinates are a set of coordinates plotted on a system that uses the distance from the origin and angle from an axis to describe location.

Rectangular Coordinates: A set of rectangular coordinates are a set of coordinates plotted on a system using basis axes at right angles to each other.

Guided Practice

1. Write the rectangular equation (x - 4)^2 + (y - 3)^2 = 25 in polar form.

2. Write the rectangular equation 3x - 2y = 1 in polar form.

3. Write the rectangular equation x^2 + y^2 - 4x + 2y = 0 in polar form.

Solutions:

1.

(x - 4)^2 + (y - 3)^2 & = 25 \\x^2 - 8x + 16 + y^2 - 6y + 9 & = 25 \\x^2 - 8x + y^2 - 6y + 25 & = 25 \\x^2 - 8x + y^2 - 6y & = 0 \\x^2 + y^2 - 8x - 6y & = 0 \\r^2 - 8(r \cos \theta) - 6(r \sin \theta) & = 0 \\r^2 - 8r \cos \theta - 6r \sin \theta & = 0 \\r(r - 8 \cos \theta - 6 \sin \theta) & = 0 \\r = 0\ \text{or}\ r - 8 \cos \theta - 6 \sin \theta & = 0 \\r = 0\ \text{or}\ r & = 8 \cos \theta + 6 \sin \theta

From graphing r-8\cos \theta -6\sin \theta =0 , we see that the additional solutions are 0 and 8.

2.

3x - 2y & = 1 \\3r \cos \theta - 2r \sin \theta & = 1 \\r (3 \cos \theta - 2 \sin \theta) & = 1 \\r & = \frac{1}{3 \cos \theta - 2 \sin \theta}

3.

x^2 + y^2 - 4x + 2y & = 0 \\r^2 \cos^2 \theta + r^2 \sin^2 \theta - 4 r \cos \theta + 2 r \sin \theta & = 0 \\r^2 (\sin^2 \theta + \cos^2 \theta) - 4 r \cos \theta + 2 r \sin \theta & = 0 \\r (r - 4 \cos \theta + 2 \sin \theta) & = 0 \\r = 0\ \text{or}\ r - 4 \cos \theta + 2 \sin \theta & = 0 \\r = 0\ \text{or}\ r & = 4 \cos \theta - 2 \sin \theta

Concept Problem Solution

The original equation to convert is:

(x + 1)^2 - (y + 2)^2 = 7

You can substitute x = r\cos \theta and y = r\sin \theta into the equation, and then simplify:

(r\cos \theta +1)^2 - (r\sin \theta + 2)^2 = 7\\(r^2\cos^2 \theta + 2r\cos \theta +1) - (r^2\sin^2 \theta + 2r\cos \theta + 4) = 7\\r^2(\cos^2 \theta + \sin^2 \theta) + 4r\cos \theta + 5 = 7\\r^2 + 4r\cos \theta = 2

Practice

Write each rectangular equation in polar form.

  1. x=3
  2. y=4
  3. x^2+y^2=4
  4. x^2+y^2=9
  5. (x-1)^2+y^2=1
  6. (x-2)^2+(y-3)^2=13
  7. (x-1)^2+(y-3)^2=10
  8. (x+2)^2+(y+2)^2=8
  9. (x+5)^2+(y-1)^2=26
  10. x^2+(y-6)^2=36
  11. x^2+(y+2)^2=4
  12. 2x+5y=11
  13. 4x-7y=10
  14. x+5y=8
  15. 3x-4y=15

Image Attributions

Description

Difficulty Level:

At Grade

Subjects:

Grades:

Date Created:

Sep 26, 2012

Last Modified:

Oct 28, 2014
Files can only be attached to the latest version of Modality

Reviews

Please wait...
Please wait...
Image Detail
Sizes: Medium | Original
 
MAT.TRG.636.L.1

Original text